The use of metaphor and certain scale patterns in traditional music of Botswana - Wood, Elizabeth N. (International Library of African Music, 1983)
Three salient characteristics observed in recorded music in Botswana have been of particular interest to me during four years of music research in this country — carried out in the Kgatleng, Kweneng and Kgalagadi Districts. These are (1) the use of metaphor in the initiation song, (2) the appearance of the five-tone scale in Tswana traditional songs and (3) the presence of the four-tone scale in Basarwa (Bushman) songs and some of their instrumental music.
Keywords: Metaphor; Music; African Music; Botswana; Traditional Music